Dirammox Is Widely Distributed and Dependently Evolved in Alcaligenes and Is Important to Nitrogen Cycle - Hou, Ting-Ting; Miao, Li-Li; Peng, Ji-Sen; Ma, Lan; Huang, Qiang; Liu, Ying; Wu, Meng-Ru; Ai, Guo-Min; Liu, Shuang-Jiang; Liu, Zhi-Pei (Frontiers in Microbiology, 2022)
Nitrogen cycle is an essential process for environmental health. Dirammox, encoded by the dnfT1RT2ABCD cluster, was a novel pathway for microbial N2 production defined in Alcaligenes ammonioxydans HO-1. Here, a copy of the cluster dnfT1RT2ABCD as a whole was proved to be existed and very conserved in all Alcaligenes genomes. Phylogenetic analyses based on 16S rRNA gene sequences and amino acid sequences of DnfAs, together with G+C content data, revealed that dnf cluster was evolved associatedly with the members of the genus Alcaligenes. Under 20% O2 conditions, 14 of 16 Alcaligenes strains showed Dirammox activity which seemed likely taxon-related. However, the in vitro activities of DnfAs catalyzing the direct oxidation of hydroxylamine to N2 were not taxon-related, but depended on the contents of Fe and Mn ions. The results indicated that DnfA is necessary but not sufficient for the Dirammox activity. The fact that members of the genus Alcaligenes are widely distributed in various environments, including soil, water bodies (both fresh and sea water), sediments, activated sludge, animal/plant associated environments, etc. strongly suggests that the Dirammox is important to nitrogen cycle and therefore to the environments. In addition, Alcaligenes species are also commonly found in wastewater treatment plants, suggesting that they might be valuable resources for wastewater treatment.